(untitled) (Research, Society and Development, 2021)
Objective: To verify the acceptance of the population in the purchase of generic drugs and the factors that may be associated. Methods: This is a descriptive study, conducted with 393 individuals, of both genders, aged between 18 and 80 years. Users were investigated for acceptance and use of generic drugs. The data obtained were entered into an Excel version 2013 spreadsheet and transferred to the IBM® SPSS® Statistics version 24.0 software. The study was approved by the Research Ethics Committee. Results: It was evident that the majority of respondents (96.5%) said they had already used a generic drug and 89.8 reported having achieved an effective result in the treatments performed with these drugs and that after use they felt that there was the desired effect. Conclusion: Generic drugs are accepted by most of the population. And the level of knowledge about generic drugs by the population has increased. The population trusts the pharmacist to switch from the branded drug to the generic one.